A nonlinear finite element analysis of soil deformation - John J. Burke (1983)
A set of finite element computer programs has been written for the settlement analysis of structures founded on normally consolidated and lightly overconsolidated soft clays. The programs take into account nonlinear material stress-strain behaviour and creep. Analyses may assume 'undrained' and 'drained' conditions and fully coupled consolidation analyses are also possible. The 'modified' Cam clay model has been used with some modification to model nonlinear material stress-strain behaviour and a phenomenological creep relationship to model creep behaviour. The author's programs have been-tested against another, fully tested, finite element package and also against closed form solutions where they exist. Sensitivity of the results of creep analyses in response to possible variations in the determination of the values of the creep parameters has also been studied. Results of a combined creep and consolidation analysis of a flexible strip footing. indicate the relative importance of creep displacements with respect to the consolidation settlements which are difficult to separate in practice. A review is made of the main nonlinear models of soil behaviour available to the practising engineer. The main techniques within the finite element method that are used to implement such nonlinear soil models are also reviewed and the 'initial strain' method chosen for use in the computer programs developed. The author's programs have been used to calculate displacements and excess pore pressures resulting from the construction of a trial embankment built at Cubzac-les-Ponts in France and compared to the measured in-situ values. In the conclusions an appraisal is made of the soil model developed by the author and the nonlinear finite element solution technique used. Also, the results of analyses using the computer programs and the accuracy of the results of the analyses of the trial embankment are summarised. The author's computer programs are explained and listed in the form of appendices.